Intention of physicians to implement guidelines for screening and treatment of latent tuberculosis infection in HIV-infected patients in The Netherlands: a mixed-method design - Evenblij, Kirsten; Verbon, Annelies; van Leth, Frank (BMC public health, 2016)
Backgound All newly diagnosed HIV-infected patients in the Netherlands should be screened for latent tuberculosis infection (LTBI) and offered preventive therapy if infected without evidence of active tuberculosis. This guideline, endorsed by the national professional body of HIV physicians is in line with international recommendations, and based on the increased risk of progression from LTBI to active tuberculosis in HIV-infected patients. The objective of the study is to assess the intention of HIV physicians to implement this national guideline. Methods A mixed method design triangulating results from two surveys among all ( n = 80) HIV physicians in The Netherlands and qualitative interviews among 11 Dutch HIV physicians performed in 2014. Results The majority of physicians used a risk-stratification approach based on individual a priori risk of tuberculosis to identify HIV-infected patients for LTBI screening, rather than screening all new HIV-infected patients. The intended and actual provision of preventive treatment was low, due to expressed doubts on the accuracy of diagnostic tools for LTBI. Interviewees reported that the guidelines did not match their clinical experience and lacked evidence for the recommendations. Screening for and treatment of LTBI was approached at a patient-level only. None of the interviewees referred to potential public health implications of the guidelines. Conclusions Intended implementation of the national HIV-TB guidelines in the Netherlands is poor, due to a disconnect between clinical practice and evidence-based recommendations in the guideline. There is an urgent need to reconcile the views of HIV-physicians, public health experts, and guideline committee members, regarding the best strategy to address HIV-TB co-infection in the Netherlands.